Anti-obesity functions of fucoidan conducted by bioinformatics and validation findings targeting of autophagy - Jinkai Li; Xiaowei Wan; Yonghang Li; Ping Wang; Jian Chen; Weihua Jin; Jiaqi Liu (Carbohydrate Polymer Technologies and Applications)
Autophagy, one of cell death mechanisms that lysosomes degrade endogenous cellular organelles and cytoplasm, is reported to regulate the development of obesity. Fucoidan, a sulfate-containing polysaccharide, is recognized for its anti-obesity effect. In our previous report, we presented the anti-obesity actions of fucoidan, however, the molecular mechanisms targeting autophagy remain unexplored. In this study, the purity, structure, and composition of compounds in fucoidan were characterized by using chemical analysis. Then, we conducted network pharmacology analysis to screen the pharmacological targets and to reveal the molecular mechanisms involved in anti-obesity action of fucoidan through targeting autophagy. Molecularly docked assay was used to further assess the spatial binding capability of fucoidan to target proteins. Our result identified core genes of fucoidan against obesity associated with autophagy. Functional enrichment analysis showed core genes involvement in metabolism, immunity, cell proliferation and differentiation, and kinase activity. Further pathway enrichment analysis chiefly comprised biological binding and immunity. Molecular docking data indicated that the key proteins resulted in potent affinities with fucoidan. Finally, in vitro adipocyte model and animal model were used to validate the preclinical findings that fucoidan suppressed adipocyte proliferation, reduced lipid deposition, induced autophagy, and inhibited adipogenic differentiation. Collectively, these bioinformatics and biochemical findings revealed the anti-obesity effects and mechanisms of fucoidan actions through targeting autophagy.